2004
DOI: 10.1359/jbmr.0301239
|View full text |Cite
|
Sign up to set email alerts
|

Cooperation Between TGF-β and Wnt Pathways During Chondrocyte and Adipocyte Differentiation of Human Marrow Stromal Cells

Abstract: Human marrow stromal cells have the potential to differentiate to chondrocytes or adipocytes. We show interactions between TGF-␤ and Wnt signaling pathways during stimulation of chondrogenesis and inhibition of adipogenesis. Combining these signals may be useful in marrow stromal cell therapies.Introduction: Human bone marrow stromal cells (hMSCs) have the potential to differentiate to lineages of mesenchymal tissues, including cartilage, fat, bone, tendon, and muscle. Agents like transforming growth factor (T… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

11
166
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 209 publications
(178 citation statements)
references
References 53 publications
11
166
0
1
Order By: Relevance
“…These findings support a recent findings demonstrating that Twist-1 interferes with BMP-2 induced expression of collagen type II and aggrecan [50]. Interestingly, the present study found that adipose accumulation and adipogenic related gene expression were enhanced in human MSC cultures following enforced expression of either Twist-1 or Dermo-1, consistent with studies showing that suppression of osteo/chondrogenesis via BMP/ TGFb signaling is associated with increased adipogenesis [50,[63][64][65][66][67]. Therefore, it is likely that a reciprocal regulation of the Twist transcription factors occurs with different BMP/TGFb and Wnt signaling components that collectively act to regulate the lineage commitment of MSC toward adipogenic or ostechondrogenic development [49,50,62,65,68].…”
Section: Discussionsupporting
confidence: 93%
“…These findings support a recent findings demonstrating that Twist-1 interferes with BMP-2 induced expression of collagen type II and aggrecan [50]. Interestingly, the present study found that adipose accumulation and adipogenic related gene expression were enhanced in human MSC cultures following enforced expression of either Twist-1 or Dermo-1, consistent with studies showing that suppression of osteo/chondrogenesis via BMP/ TGFb signaling is associated with increased adipogenesis [50,[63][64][65][66][67]. Therefore, it is likely that a reciprocal regulation of the Twist transcription factors occurs with different BMP/TGFb and Wnt signaling components that collectively act to regulate the lineage commitment of MSC toward adipogenic or ostechondrogenic development [49,50,62,65,68].…”
Section: Discussionsupporting
confidence: 93%
“…64,65 NELL-1 reduction of PPARg expression was blocked by canonical Wnt inhibitors, indicating that NELL-1 down-regulation of adipogenesis was dependent on intact Wnt signaling. It was recently reported that BMP2 represses Wnt signaling during bone repair in a 1-mm in vivo monocortical trephine defect model.…”
Section: Proposed Molecular Mechanisms Of Nell-1 and Bmp2 Effects On mentioning
confidence: 99%
“…A study with hMSCs showed that TGF-b and Wnt cooperatively stimulate their proliferation and inhibit their differentiation to osteoblasts. 30,33 We reported that crosstalk between TGF-b and Wnt signaling regulates chondrocyte 20 and adipocyte 20,34 differentiation, and that TGF-b1 activates b-catenin signaling pathway and modulates osteoblastogenesis in hMSCs. 31 Crosstalk between BMP and Wnt can be synergistic or antagonistic depending on the context.…”
Section: Discussionmentioning
confidence: 99%
“…Western immunoblotting was performed as described. 20 The primary antibody anti-b-catenin (E5), anti-b-actin, and the second antibody anti-mouse IgG-HRP were purchased from Santa Cruz Biotechnology (Santa Cruz, CA). The antibody-associated protein bands were revealed with the ECL-plus Western immunoblotting system (Amersham Biosciences, Little Chalfont, UK).…”
Section: Western Immunoblotmentioning
confidence: 99%